HUBUNGAN FAKTOR PSIKOSOSIAL DENGAN KEJADIAN SKIZOFRENIA - Sihaloho, Fahala L.; Tiji, Wijaya T.; Tarigan, Menang B. (Universitas Methodist Indonesia, 2021)
Background: Schizophrenia is a chronic mental disorder that affects people's thoughts, feelings, and behavior. Psychosocial is one of the things considered in healing or relapse of schizophrenia. Method : Study literature review comparing about 11 related journals Result: Among these 11 journals, several studies agree and some are contradictory that psychosocial factors are corrilated with the incidence of schizophrenia Conclusion: Psychosocial factors have a significant correlation with healing and prevention of relapse of schizophrenia patients